Carbonic Anhydrase 1-Mediated Calcification Is Associated With Atherosclerosis, and Methazolamide Alleviates Its Pathogenesis - Yuan, Lin; Wang, Minghua; Liu, Tianqi; Lei, Yinsheng; Miao, Qiang; Li, Quan; Wang, Hongxing; Zhang, Guoqing; Hou, Yinglong; Chang, Xiaotian (Frontiers in Pharmacology, 2019)
Vascular calcification is an important pathogenic process in atherosclerosis (AS); however, its immediate cause is unknown. Our previous study demonstrated that carbonic anhydrase 1 (CA1) stimulates ossification and calcification in ankylosing spondylitis and breast cancer. The current study investigated whether CA1 plays an important role in AS calcification and whether the CA inhibitor methazolamide (MTZ) has a therapeutic effect on AS. We successfully established an AS model by administration of a high-fat diet to ApoE-/- mice. The treated animals had significantly increased serum levels of high-density lipoprotein cholesterol (HDL-c) and nitric oxide (NO) and decreased serum concentrations of total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-c), IL-6, interferon (IFN)-γ, granulocyte-macrophage colony-stimulating factor (GM-CSF), tumor necrosis factor-α (TNF-α), chemokine (C-X-C motif) ligand 1/keratinocyte-derived chemokine (CXCL1/KC) and C-C motif chemokine ligand 2 (CCL2)/monocyte chemoattractant protein 1 (MCP-1). The treated mice also had reduced AS plaque areas and fat accumulation, with no clear calcium deposition in the intima of the blood vessels. CA1 expression was significantly increased in the aortic lesions, particularly in calcified regions, but the expression was dramatically lower in the mice that received MTZ treatment or MTZ preventive treatment. CA1 was also highly expressed in human AS tissues and in rat vascular smooth muscle cells (VSMCs) with β-glycerophosphate (β-GP)-induced calcification. Acetazolamide (AZ), a CA inhibitor with a chemical structure similar to MTZ, markedly suppressed calcification and reduced CA1, IL-6, IFN-γ, GM-CSF and TNF-α expression in cultured VSMCs. Anti-CA1 siRNA significantly suppressed calcification, cell proliferation and migration, promoted apoptosis, and reduced IL-6, IFN-γ, GM-CSF and TNF-α secretion in cultured VSMCs. These results demonstrated that CA1 expression and CA1-mediated calcification are significantly associated with AS progression. MTZ significantly alleviated AS and suppressed CA1 expression and proinflammatory cytokine secretion, indicating the potential use of this drug for AS treatment.